(untitled) (Globalization and Business, 2023)
COVID-19 has become a global problem affecting all countries of the world. The pandemic covered all areas: medicine,economics, tourism, culture, etc., including agriculture. Closing markets, banning transport, and various economic restrictions haveeffectively hampered agricultural workers. The field of agriculture is important for Georgia because many people are employedin this sector and the well-being of many families is directly related to the development of this field. Added to this is the fact thatagriculture is a kind of tradition and culture for Georgia, which has been followed by the nation for many centuries and whichis bloodied with the Georgian identity. Therefore, the impact of COVID-19 in this area is especially important for Georgia. In thecontext of the global pandemic, various problems and challenges have been identified in all areas, including agriculture. Along witha number of negative aspects, such as economic instability, problems in export-import of products, etc., which negatively affectthe development of agriculture, there are also positive circumstances: the ability to control quality, focus more on food safety,accelerate digitization and popularization, popularization, and popularization.